Respuestas
Respuesta dada por:
0
Solución:
8⁽ˣ⁻¹⁾ / 2⁽³⁻ˣ⁾ = 64 * 4ˣ
2³⁽ˣ⁻¹⁾ / 2⁽³⁻ˣ⁾ = 2⁶ * 2²ˣ
2³⁽ˣ⁻¹⁾⁻⁽³⁻ˣ⁾ = 2⁶⁺²ˣ
2³ˣ⁻³⁻³⁺ˣ = 2⁶⁺²ˣ
2⁴ˣ⁻⁶ = 2⁶⁺²ˣ
4x - 6 = 6 + 2x
4x - 2x = 6 + 6
2x = 12
x = 12 / 2
x = 6
8⁽ˣ⁻¹⁾ / 2⁽³⁻ˣ⁾ = 64 * 4ˣ
2³⁽ˣ⁻¹⁾ / 2⁽³⁻ˣ⁾ = 2⁶ * 2²ˣ
2³⁽ˣ⁻¹⁾⁻⁽³⁻ˣ⁾ = 2⁶⁺²ˣ
2³ˣ⁻³⁻³⁺ˣ = 2⁶⁺²ˣ
2⁴ˣ⁻⁶ = 2⁶⁺²ˣ
4x - 6 = 6 + 2x
4x - 2x = 6 + 6
2x = 12
x = 12 / 2
x = 6
Respuesta dada por:
1
Se trata de una ecuación exponencial
Aplicando propiedades operatorias de potencias
![\frac{8 ^{(x-1)} } {2^{(3-x)} } =64*4^x \\ \\ \frac{ 2^{3(x-1)} }{ 2^{(3-x)} } =2^6*2 ^{2x} \\ \\ 2^{(3x-3)-(3-x)} = 2^{2x+6} \\ \\ 2^{3x-3-3+x} = ^{2x+6} \\ \\ 4x-6=2x+6 \\ \\ 2x=12 \\ \\ x= \frac{12}{2} \frac{8 ^{(x-1)} } {2^{(3-x)} } =64*4^x \\ \\ \frac{ 2^{3(x-1)} }{ 2^{(3-x)} } =2^6*2 ^{2x} \\ \\ 2^{(3x-3)-(3-x)} = 2^{2x+6} \\ \\ 2^{3x-3-3+x} = ^{2x+6} \\ \\ 4x-6=2x+6 \\ \\ 2x=12 \\ \\ x= \frac{12}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B8+%5E%7B%28x-1%29%7D+%7D+%7B2%5E%7B%283-x%29%7D+%7D+%3D64%2A4%5Ex+%5C%5C++%5C%5C++%5Cfrac%7B+2%5E%7B3%28x-1%29%7D+%7D%7B+2%5E%7B%283-x%29%7D+%7D+%3D2%5E6%2A2+%5E%7B2x%7D++%5C%5C++%5C%5C++2%5E%7B%283x-3%29-%283-x%29%7D+%3D+2%5E%7B2x%2B6%7D++%5C%5C++%5C%5C++2%5E%7B3x-3-3%2Bx%7D+%3D+%5E%7B2x%2B6%7D++%5C%5C++%5C%5C+4x-6%3D2x%2B6+%5C%5C++%5C%5C+2x%3D12+%5C%5C++%5C%5C+x%3D+%5Cfrac%7B12%7D%7B2%7D+)
RESULTADO FINAL
Aplicando propiedades operatorias de potencias
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años